Evaluation of Genomic DNA Extraction Using Monolayer and Bilayer Magnetic Nanoparticles - Hadiseh Rostami (Alborz University of Medical Sciences, 2020)
Background: There are different methods for genomic DNA extraction. Magnetic nanoparticles (MNPs) exhibit many important features making them suitable for DNA extraction. Objectives: The aim of this study was to compare the effect of monolayer and bilayer MNPs on genomic DNA extraction. Materials and Methods: The genomic DNA was extracted from the Staphylococcus aureus strain ATCC 25923 and clinical isolates using monolayer MNPs SiO2 and Fe3O4 and bilayer MNPs SiO2/Fe3O4. Then, the quality and quantity of the obtained genomic DNA were compared with both NPs. Results: The obtained results showed the concentration and purity of the extracted genomic DNA using bilayer magnetic NPs was significantly higher in comparison to the extracted genomic DNA by monolayer MNPs. Conclusion: In general, surface-coated MNPs are much more efficient than naked MNPs for genomic DNA extraction.